PENINGKATAN PEMAHAMAN QRIS BAGI PELAKU UMKM MELALUI WEBINAR EDUKASI PEMBAYARAN DIGITAL DALAM MENDUKUNG TRANSFORMASI KEUANGAN - Arif Budi Sulistyo; Rudiyanto Rudiyanto; Sev Rahmiyanti; Maman Suryaman; Hartadi Wijaya; Nur Hidayanti; Zaldy Suhatman; Dadang Romansyah; Dika Putri Meidiana; Duwi Cahyati (Nindikayla Institute, 2026)
The development of the digital economy encourages MSME actors to adapt to various technological innovations, including the use of digital payment systems. However, the results of initial observations show that some MSME actors still have limited understanding of digital payments and the use of the Quick Response Indonesian Standard (QRIS), and still rely on cash transactions in their business activities. This Community Service (PkM) activity aims to increase participants' understanding of digital payment systems, introduce QRIS as a national standard for digital payments, provide an understanding of the benefits and security of QRIS, and encourage the use of digital transactions in supporting the financial transformation of MSMEs. The activity was carried out in the form of an online webinar organized by the Indonesian Institute of Accountants of the Banten Region with the theme